Synthetic Cannabinoids: Pharmacology, Behavioral Effects, and Abuse Potential - Tai, Sherrica (Curr Addict Rep, 2014)
Cannabis has been used throughout the world for centuries. The psychoactive effects of cannabis are largely attributable to Δ(9)-tetrahydrocannabinol (Δ(9)-THC), the prototypical cannabinoid that occurs naturally in the plant. More recently, chemically- and pharmacologically-distinct synthetic cannabinoids (SCBs) have emerged as drugs of abuse. As compared to Δ(9)-THC, the distinct structures of these compounds allow them to avoid legal restrictions (at least initially) and detection in standard drug screens. This has contributed to the popularity of SCBs among drug users who seek to avoid positive drug screens. Importantly, the distinct structures of the SCBs also typically result in increased affinity for and efficacy at cannabinoid CB1 receptors, which are thought to be responsible for the psychoactive effects of Δ(9)-THC and its analogues. Accordingly, it seems likely that these more powerful cannabimimetic effects could result in increased adverse reactions and toxicities not elicited by Δ(9)-THC in cannabis. Animal models useful for the study of emerging SCBs include the cannabinoid tetrad, drug discrimination, and assays of tolerance, dependence, and withdrawal. However, these in vivo procedures have not been particularly informative with regards to drug efficacy, where the majority of SCB effects are comparable to those of Δ(9)-THC. In contrast, essentially all in vitro measures of drug efficacy confirm Δ(9)-THC as a relatively weak CB1 partial agonist, while the majority of the SCBs detected in commercial preparations are full agonists at the CB1 receptor. As use of these emerging SCBs continues to rise, there is an urgent need to better understand the pharmacology and toxicology of these novel compounds.